PENINGKATAN PROFESIONALISME MANAJEMEN KEUANGAN MELALUI INVESTASI UNTUK MASA DEPAN PERUSAHAAN - Kus Irawan Prabowo; Muhammad Zen Masruri; Yulian Adi Wijaya (JURNAL INOVASI SAINS TEKNOLOGI DAN BISNIS, 2025)
This study seeks to assess how income and risk tolerance influence investing decisions, with financial literacy serving as an indirect relationship. Two critical aspects impact investor behavior when making investing decisions: income sufficiency and risk management competence. Financial literacy (the capacity to understand financial instruments) is seen as an intermediary element that improves the link between income, risk tolerance, and investment decisions. This study investigated using Structural Equation Modeling. The findings indicate that risk tolerance and income have a substantial role in investment decisions. Furthermore, financial literacy acts as a mediating variable, implying that higher levels of financial knowledge increase the effect of income and risk tolerance on investing decisions.